Growth, Spectral, Electrical, Photoluminescence, Thermal, Mechanical and Dielectric Studies of 2-Hydroxy Benzoic Acid (Metabolite of Drug Aspirin) Single Crystal (Journal of Scientific Research, 2025)
2-Hydroxy benzoic acid (2-HBA) is the metabolite of the drug aspirin. The slow evaporation approach was employed to grow the 2-HBA block crystal.  Throughout the visible and near-infrared wavelength ranges, the crystal exhibits exceptionally excellent optical transmittance of 99 %. Optical parameters like transmittance, optical absorption coefficient, absorbance, reflectance, optical conductivity, extinction coefficient, refractive index, electrical conductivity, as well as crystal’s band gap energy had been computed from UV-Vis-NIR spectrum. From the photoluminescence investigation, violet emission appears at 375 nm. As per the thermogravimetric investigation, the material exhibits stability up to 160 ºC. Vickers microhardness was employed in a mechanical investigation to determine the crystal's elastic stiffness constant, yield strength, as well as work hardening coefficient. Crystal is categorized as a hard material if its work hardening index (n) is less than 2. The Laser damage threshold of 2-HBA crystal is 15.5086 GW/cm2. This study shows that the 2-HBA crystal exhibits excellent optoelectronics application. The dielectric constant along with dielectric loss is assessed as a function of the frequency.